Toward a safe supply chain: Incorporating accident, physical, psychosocial and mental overload risks into supply chain network - Karimi, Sajad; Ardalan, Zaniar; Poursabzi, Omid; Naderi, B. (Environment, development and sustainability, 2023)
Considering health and safety factors in supply chain network design brings safer place for employee and helps firm to have better image in the society. There are many health and safety factors overlooked by literature studies of supply chain. This paper takes advantage of the results of occupational safety and health in the transport sector studies and connects this field of science with the supply chain network design. This study incorporates health and safety factors such as accident, physical, psychosocial and mental overload risks as an objective function besides cost- and environmental-oriented objective functions. We formulated a multi-objective closed-loop supply chain network as a mixed integer linear programming model and customized augmented epsilon constraint algorithm to solve our multi-objective problem to offer multiple choices for decision makers. Eventually, we analyzed the effects of incorporating health and safety factors in supply chain and demonstrated how it will minimize the health and safety risks of supply chain employees, environmental pollution and the total cost of the network simultaneously.